The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/cts.12915
|View full text |Cite
|
Sign up to set email alerts
|

Role for Drug Transporters in Chemotherapy‐Induced Peripheral Neuropathy

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a common and dose-limiting toxicity to widely used chemotherapeutics. Although the exact molecular mechanism of chemotherapy-induced peripheral neuropathy remains elusive, there is consensus that it is caused by damage to the peripheral nervous system leading to sensory symptoms. Recently developed methodologies have provided evidence of expression of drug transporters in the peripheral nervous system. In this literature review, we explore the role for drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 76 publications
2
19
0
Order By: Relevance
“…Over the last 5−10 years, preclinical data have identified the transporters responsible for the development of CIPN, such as oxaliplatin and paclitaxel [ 84 , 85 , 86 , 87 ]. However, it remains unclear which transporter is responsible for bortezomib accumulation in the DRG [ 88 ]. Additionally, it is also unknown which cell type (sensory neurons, macrophages, satellite glial cells, or others) uptakes bortezomib, leading to the development of BIPN.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Over the last 5−10 years, preclinical data have identified the transporters responsible for the development of CIPN, such as oxaliplatin and paclitaxel [ 84 , 85 , 86 , 87 ]. However, it remains unclear which transporter is responsible for bortezomib accumulation in the DRG [ 88 ]. Additionally, it is also unknown which cell type (sensory neurons, macrophages, satellite glial cells, or others) uptakes bortezomib, leading to the development of BIPN.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Thus, compounds that prevent OATP1B2- [ 72 ] and OCT2-dependent [ 73 , 74 ] uptake of paclitaxel and oxaliplatin, respectively, may have the potential to protect against CIPN. The ability of dasatinib inhibition of OCT2 to prevent oxaliplatin-induced peripheral neuropathy in patients with colorectal cancer [ 74 , 75 ] is currently being evaluated in a clinical trial (ClinicalTrial.gov identifier: NCT04164069; open to recruitment at the time of writing).…”
Section: Pathophysiology Of Cancer Treatment-related Pain Syndromesmentioning
confidence: 99%
“…For many small-molecule anticancer drugs, this process is mediated by uptake transporters located in DRG neurons, and ongoing efforts attempt to block these transporters, reduce intra-neuronal concentrations of the neurotoxic agents, and ultimately protect against a dose-limiting injury. The role of drug transporters in CIPN was recently extensively reviewed [ 13 ], and this field of research will be illustrated here for oxaliplatin and paclitaxel, two agents for which defined transporters have been identified that can be targeted pharmacologically.…”
Section: Pharmacological Strategies For Prevention/treatment Of CImentioning
confidence: 99%
“…Preceding investigations have found that facilitated transport mechanisms are responsible for the neuronal uptake of platinum-based chemotherapeutic drugs associated with CIPN such as oxaliplatin [ 14 ]. Although recent have suggested emerging importance of multiple solute carriers in oxaliplatin neurotoxicity, including the organic cation transporters novel 1 (OCTN1) and multidrug and toxin extrusion 1 (MATE1), the actual in vivo contribution of these proteins to CIPN has remained inconclusive [ 13 ]. Using transporter-deficient mouse models, it was recently suggested that the direct contribution of OCTN1 and MATE1 to oxaliplatin neurotoxicity is negligible and that the neuronal uptake of oxaliplatin and the subsequent neurotoxicity is predominantly mediated by the related transporter organic cation transporter 2 (OCT2) [ 15 ].…”
Section: Pharmacological Strategies For Prevention/treatment Of CImentioning
confidence: 99%